Current issues of science and research in the global world : proceedings of the International Conference on Current Issues of Science and Research in the Global World, Vienna, Austria, 27-28 May 2014 /: proceedings of the International Conference on Current Issues of Science and Research in the Global World, Vienna, Austria, 27-28 May 2014. (2014) - Unknown
No abstract available